Delayed surgical treatment of supracondylar humerus fractures in children using a medial approach - (:unkn) unknown (My University, 2008)
Purpose The appropriate management of supracondylar humerus fractures in children is frequently delayed due to various factors, and there is still no agreement on the treatment of choice. The purpose of this study was to evaluate the effects of delayed treatment of displaced supracondylar humerus fractures on the treatment results and complication rate. Methods A total of 31 children with supracondylar humerus fractures who had not received adequate treatment for their displaced fractures were included in this study. The conditions leading to delayed treatment mainly included severe swelling or skin problems around the elbow and the health facility problems unique to our district. The mean delaying time was 6 days (range 2–19 days). There were 24 males and 7 females with a mean age of 7 years (range 1–13 years). The fractures were classified as type III-A ( n = 15; 48%) and type III-B ( n = 16; 52%) according to Gartland. Surgical treatment consisting of sentiment manual reduction through a medial approach and percutaneous cross-pinning was applied to all. No image intensifier was used during the procedures. A long-arm splint was used for post-operative immobilization. Results The average hospital stay was 2 days (range 1–3 day) and the patients were followed clinically and radiographically for an average of 4 years (range 2–11 years). Pins were removed at the end of the third week post-operatively, at which time the range of motion exercises were begun. None of the patients required physical therapy and full functional recovery was achieved within 3 months in 29 (93.5%) patients and within 5 months in the remaining 2 (6.5%). Two (6.5%) pre-operative nerve injuries (1 interosseous, 1 ulnar) were resolved spontaneously within 3 months post-operatively. At the final follow-up, 7 (22.5%) patients had cubitus varus deformity. Except for 2 (6.5%) pin-tract infections, which were resolved by oral antibiotics and pin removal, none of the patients had early or late complications, not even neurological deficit or myositis ossificans. Conclusions Delayed presentation of displaced supracondylar humerus fractures in children did not increase complication rates or unsatisfactory results following an open reduction. Medial approach and cross-pinning is an effective and reliable treatment method for these fractures.